Misconception in exponential numbers in IST and IIND level primary school mathematics - Ozkan, Erdogan Mehmet; Ozkan, Ayten (ELSEVIER SCIENCE BV, 2012)
The aim of this study was to determine misconceptions Ist and IInd level primary school students about exponential numbers. The sample of study consists of the students of a high school, 4 primary schools and a SBS and OSS training center. A questionnaire was administered to collect data. According to the result of the study, it is seen that the students have misconceptions about exponential numbers. Some solutions are recommended to those students to overcome such difficulties. (C) 2012 Published by Elsevier Ltd. Selection and/or peer review under responsibility of Prof. Dr. Huseyin Uzunboylu
Keywords: Mathematics Education; Root Numbers; Misconceptions; Education & Educational Research